2022
DOI: 10.3390/cells11010138
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Quantitative Phosphoproteomics Profiling of Interleukin-33 Signaling Network Reveals Unique Modulators of Monocyte Activation

Abstract: Interleukin-33 (IL-33), a member of the IL-1 superfamily cytokines, is an endogenous danger signal and a nuclear-associated cytokine. It is one of the essential mediators of both innate and adaptive immune responses. Aberrant IL-33 signaling has been demonstrated to play a defensive role against various infectious and inflammatory diseases. Although the signaling responses mediated by IL-33 have been previously reported, the temporal signaling dynamics are yet to be explored. To this end, we applied quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Proteomic and phosphoproteomic datasets were mapped onto templates for IL5 and IL33 signaling pathway ( Figure 5) using the KEGG Database, WikiPathways, and published networks 3539 . We first identified eosinophil-expressed proteins identified in at least one of the three datasets ( Supplemental Spreadsheet 1 ) and then mapped phosphorylated proteins and significantly changing sites in the IL33-versus-IL5 phosphoproteomic dataset to pathways of interest ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic and phosphoproteomic datasets were mapped onto templates for IL5 and IL33 signaling pathway ( Figure 5) using the KEGG Database, WikiPathways, and published networks 3539 . We first identified eosinophil-expressed proteins identified in at least one of the three datasets ( Supplemental Spreadsheet 1 ) and then mapped phosphorylated proteins and significantly changing sites in the IL33-versus-IL5 phosphoproteomic dataset to pathways of interest ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Special consideration is required during protein extraction where the cell lysis buffer should include phosphatase inhibitors such as sodium orthovanadate, sodium pyrophosphate and beta-glycerophosphate. 322 Enrichment can be done at the protein level before proteolysis. Phosphoprotein enrichment typically involves the use of immobilized metal-affinity chromatography (IMAC) to selectively capture phosphorylated proteins based on their high-affinity binding to metal ions such as Ga(III), Fe(III), Zn(II) and Al(III).…”
Section: Peptide Enrichmentmentioning
confidence: 99%
“…As with any proteomics experiment, phosphoproteomics studies require protein extraction, proteolytic enzyme digestion, phosphopeptide enrichment, peptide fractionation, LC-MS/MS, bioinformatics data analysis, and biological function inference. Special consideration is required during protein extraction where the cell lysis buffer should include phosphatase inhibitors such as sodium orthovanadate, sodium pyrophosphate and beta-glycerophosphate …”
Section: Enrichment and Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of functional analysis suggested IL-33-induced Rho-dependent signaling. Further, this research group applied quantitative temporal phosphoproteomics analysis and identified several kinases and phosphatases regulated across timepoints; they found that IL-33 regulated phosphorylation sites on transcription factors, which revealed several cellular processes of IL-33 activation, including leukocyte adhesion, response to reactive oxygen species, cell cycle checkpoints, and DNA damage and repair pathways [ 139 ]. As technology advances, a more detailed and complete IL-33 signaling network will be achieved.…”
Section: Extracellular Il-33-induced Signaling Pathwaysmentioning
confidence: 99%